2018
DOI: 10.1080/1369183x.2018.1535313
|View full text |Cite
|
Sign up to set email alerts
|

Turning citizens into immigrants: state practices of welfare ‘cancellations’ and document retention among EU nationals living in Glasgow

Abstract: This article examines the everyday experiences of welfare provision among EU migrants living in Glasgow, demonstrating how the process of restricting the rights of EU citizens has occurred well before Brexit. It is based on 12 months of ethnographic research conducted in 2012 with Czech and Slovak nationals who came to the UK after 2004. Introducing the migrants' notion of zkancelovali, the paper highlights a heightened sense of insecurity in their everyday lives, which arise from the increasingly common exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…At the same time, studies have also shown how the questioning of EU citizens' rights and entitlements has taken place beyond the level of policy and discourses as they are being enacted in mundane practices and everyday interactions with British state authorities. A study conducted in 2012 that focused on everyday experiences of welfare provision among Czech and Slovak nationals in Glasgow, for example, found how these nationals had their welfare payments frequently “cancelled” and their ID documents retained by U.K. welfare authorities, often without any explanation given (Guma, ). As well as hindering migrants' access to welfare and other state services, these document retention practices also impeded their “free movement” rights to cross national borders within the EU.…”
Section: European Migration—mobility Settlement and Belongingmentioning
confidence: 99%
“…At the same time, studies have also shown how the questioning of EU citizens' rights and entitlements has taken place beyond the level of policy and discourses as they are being enacted in mundane practices and everyday interactions with British state authorities. A study conducted in 2012 that focused on everyday experiences of welfare provision among Czech and Slovak nationals in Glasgow, for example, found how these nationals had their welfare payments frequently “cancelled” and their ID documents retained by U.K. welfare authorities, often without any explanation given (Guma, ). As well as hindering migrants' access to welfare and other state services, these document retention practices also impeded their “free movement” rights to cross national borders within the EU.…”
Section: European Migration—mobility Settlement and Belongingmentioning
confidence: 99%
“…Rzepnikowska 2018; Guma and Jones 2018). Polish children in Glasgow also received name-calling (Guma 2018) and similarly to other EU migrants were reportedly afraid to speak their language (Guma and Jones 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Barbulescu (), these countries gradually started to hollow out freedom of movement rights by, for instance, introducing measures to limit access to social benefits, and deporting homeless EU citizens. This has been documented in the UK with respect to Check and Slovak migrants who have been subjected to several instances of welfare “cancellation” and widespread and prolonged arbitrary retention of documents (Guma, ). Progressively, also, the mobility of EU citizens from older member states has started to be contested.…”
Section: Contextualizing Free Movers In Brexit Britainmentioning
confidence: 96%
“…Two years on from the referendum, the legal status of EU nationals in the UK remains unclear (D'Angelo and Kofman, ). Simultaneously, in public discourse EU nationals have been demoted from “EU citizens” to (unwelcome) “migrant workers” (D'Angelo and Kofman, ; Guma, ; Lafleur and Mescoli, ; Ranta and Nancheva, ).…”
Section: Contextualizing Free Movers In Brexit Britainmentioning
confidence: 99%
See 1 more Smart Citation